Implementasi Nilai-Nilai Islam dalam Mendorong Kesetaraan Gender di Pendidikan: Studi Literatur dan Studi Kasus - Fia Khamidatul Maula; Rahma Safina; Arizal Fatur Rahmadika; Mu’alimin Mu’alimin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Gender equality in education is a critical issue, particularly in the context of Islamic education. This study aims to explore the concepts, implementation, and challenges of gender equality based on literature analysis and case studies. The research employed a qualitative approach with a literature review method, involving 20 articles from reputable journals, with 5 selected for in-depth analysis. The findings reveal that Islamic education strongly upholds the principle of gender equality, as reflected in the values of *rahmatan lil 'alamin*. Inclusive policies, such as mixed-gender classrooms and equal leadership opportunities, have proven effective in overcoming cultural barriers and gender stereotypes. However, challenges such as conservative interpretations of religious teachings and the influence of patriarchal cultures remain significant obstacles. This study contributes to the literature on gender equality, emphasizing the role of Islamic education as a tool for social transformation. Future research is recommended to expand geographic coverage and incorporate empirical data to deepen understanding of gender equality implementation in various cultural contexts.